2016
DOI: 10.3934/dcds.2016.36.3961
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the boundedness of semilinear Duffing equations at resonance

Abstract: We introduce a new method for the boundedness problem of semilinear Duffing equations at resonance. In particular, it can be used to study a class of semilinear equations at resonance without the polynomial-like growth condition. As an application, we prove the boundedness of all the solutions for the equationẍ + n 2 x + g(x) + ψ(x) = p(t) under the Lazer-Leach condition on g and p, where n ∈ N + , p(t) and ψ(x) are periodic and g(x) is bounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In 2016, Wang, Wang and Piao [13] showed that if ψ oscillates periodically in x, the Lazer-Leach condition (1.7) is sufficient and necessary for the boundedness of (1.8).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Wang, Wang and Piao [13] showed that if ψ oscillates periodically in x, the Lazer-Leach condition (1.7) is sufficient and necessary for the boundedness of (1.8).…”
Section: Introductionmentioning
confidence: 99%